Determinant Factor of Saving Decision in Syaria Financial Institution - Hidhayati, Fitri Nur; Rahmawan, Ginanjar (CV. Inara, 2021)
This research was conducted to determine that the decision to save in Islamic cooperatives is influenced by several factors such as promotion, service quality and products. Variables used in this study are as follows promotion (X1), service quality (X2), product (X3) and decision to save (Y). This research was conducted with a quantitative approach which is one of the methods used to assess a particular population or sample by using a purposive sampling technique using a solvin count so that 88 respondents who are already members of BMT Surya Dana Makmur can be taken. Data collection techniques are by distributing questionnaires online to members using a Likert scale to make it easier for respondents to fill out. The data analysis used is multiple linear regression analysis. Researchers used a tool called SPSS (Statistical Package for Social Science) to see the results of the data obtained. The results of this study promotion have a positive and insignificant effect on the decision to save in Islamic cooperatives. Then the quality of service and products has a positive and significant effect on the decision to save in Islamic cooperatives.